Non-Judicial Activities of the Indonesian Constitutional Court: Do They Foster Judicial Reputation? - Salman, Radian; Hamdi, M. Adib Akmal; Ristawati, Rosa; Hardt, Sascha (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The Indonesian Constitutional Court is defined as a judicial body with specific competencies as stated in the 1945 Constitution. Given its significance and the heightened attention it receives from the public, the rulings of independent courts and impartial judges are vital for maintaining the reputation of the Indonesian judiciary and the public's confidence in its work. In addition to adjudicating cases, the Constitutional Court and its judges are involved in various non-judicial activities. This research article explores the reasons behind the Constitutional Court’s engagement in these activities, outlines the various types of non-judicial actions, and evaluates their effect on the court's reputation. The aim of this research is to establish a conceptual framework and assess the influence of non-judicial activities on judicial reputation by utilizing conceptual, statutory, and comparative frameworks, supported by empirical data from official documents.Top of Form The results show that the court participates in non-judicial activities to obtain benefits like increased popularity, public interest, visibility, preventing its decisions from being overturned by other judicial entities, and enhancing its reputation and influence. Often, these activities involve promoting the court's work to both local and international judicial communities to foster dialogue and connections with similar courts and stakeholders. Furthermore, non-judicial activities can influence public interest and engagement. While these initiatives benefit the institution, judges, and the public, they do not inherently improve the Constitutional Court's reputation, as its standing fundamentally relies on the quality of its decisions and its credible independence, impartiality, and integrity.